Methyl-β-cyclodextrins preferentially remove cholesterol from the liquid disordered phase in giant unilamellar vesicles - Sánchez, Susana A. (2011)
Methyl-β-cyclodextrins (MβCDs) are molecules that are extensively used to remove and to load cholesterol (Chol) from artificial and natural membranes; however, the mechanism of Chol extraction by MβCD from pure lipids or from complex mixtures is not fully understood. One of the outstanding questions in this field is the capability of MβCD to remove Chol from lipid domains having different packing. Here, we investigated the specificity of MβCD to remove Chol from coexisting macrodomains with different lipid packing. We used giant unilamellar vesicles (GUVs) made of 1,2- dioleoylphosphatidylcholine:1,2-dipalmitoylphatidylcholine:free cholesterol, 1:1:1 molar ratio at 27°C. Under these conditions, individual GUVs present Chol distributed into l o and l d phases. The two phases can be distinguished and visualized using Laurdan generalized polarization and two-photon excitation fluorescence microscopy. Our data indicate that MβCD removes Chol preferentially from the more disordered phase. The process of selective Chol removal is dependent on the MβCD concentration. At high concentrations, MβCD also removes phospholipids.